Cash Flow Ratio Analysis Before and During The COVID-19 - Taruna, Karina Rachmawati; Nindiasar, Avininda Dewi (Universitas Muhammadiyah Yogyakarta, 2023)
Introduction – This study analyzes cash flow ratios before and after the Covid-19 using cash flow ratio analysis for CPO companies listed on the IDX. Efforts to maintain the strategic role of the palm oil commodity as one of the pillars of Indonesia's economic development. Issuers of crude palm oil (CPO) plantations released financial performance in 2020 with unsatisfactory results due to commodity price pressures due to the Covid-19 causing net profit to experience a considerable decline, and even posting losses. The Coronavirus pandemic has significantly impacted the cash flow of companies in Indonesia. Purpose – This study aims to determine whether there are significant differences in the operating cash flow ratio before and after the Covid-19 for CPO companies listed on the IDX. Methodology/Approach - This research was conducted using quantitative methods, and data collection was carried out using secondary data obtained from the company's annual financial reports. The population of this study was companies in the oil palm plantation sector (CPO) that listed on IDX before the covid-19 in 2019 and during the covid-19 in 2020. Findings – The results of this study used a paired sample t-test which showed that there was a significant difference in the current ratio of cash before the pandemic and after the covid-19, namely 1) the ratio of operating cash flow caused by the company's inability to pay current debts by relying only on cash from operations, 2) the ratio of capital expenditures caused by opening new land and financing research, 3) the ratio of total debt caused by the company not being able to pay all debts solely by relying on operating cash, and 4) the ratio of operating cash flow to profit due to the closing of the market in the European Union due to the lockdown. Originality/Value/Implication - This paper is a pioneering initiative in assessing the impact of the COVID-19 on financial health through cash flow analysis based on empirical data.